GRADUATES’ PERCEPTION OF TOURISM AND HOSPITALITY DEGREE PROGRAM RELEVANCE TO CAREER ATTAINMENT: A CASE OF GRADUATES FROM THREE STATE UNIVERSITIES IN ZIMBABWE - Tapfuma, Musawenkosi; Chikuta, Oliver; Ncube, Felicity N; Baipai, Rudorwashe; Mazhande, Precious; Basera, Vitalis (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2021)
The process of making career choices is complex since there are diverse factors affecting students’ selection of programs when they enrol in higher and tertiary institutions. Just like in any other discipline, tourism and hospitality management graduates are affected by various factors when deciding their careers post-graduation. Preliminary studies have shown that a significant percentage of tourism and hospitality graduates divert from tourism to some other, sometimes totally unrelated, industries for employment. This study seeks to discover tourism and hospitality degree graduates’ perceptions and career attainment in Zimbabwe. The following critical questions were asked in order to achieve the objective of the study; Why do they enrol for the tourism/hospitality program in the first place, that is what factors affect the students’ selection process of tertiary education programs? and why do some end up in totally different fields after graduating? Qualitative research approach was adopted in order to understand the graduates’ perceptions, data was collected by the way of interviews. Data was analysed using the thematic approach. Findings revealed that while most of the graduates are employed in the tourism and hospitality industry in Zimbabwe, they are not satisfied with their jobs. Some feel that they studied tourism/hospitality as a last resort hence they do not have satisfaction while others are only in the industry because they do not have an option. Poor working conditions and poor remuneration were also cited as causes of dissatisfaction. There are however a significant number who do not regret their career choice.